Tax Compliance Ditinjau dari Theory of Planned Behavior (TPB): Studi Empiris Pada Wajip Pajak Orang Pribadi dan Badan yang Terdaftar Pada KPP di Kota Palembang - Desy Lesmana; Delfi Panjaitan; Mutiara Maimunah (Universitas Trunojoyo Madura, 2017)
This study aims to analyze the factors that affect the tax compliance by using Theory of Planned Behavior Approach (TPB). This study used survey design with data collection techniques by using questionnaires, where the selected respondents are taxpayers of individuals and entities registered at the KPP in the city of Palembang. The results showed that the variables that influence the intention to abide positively are the control behavioral variable and moral obligation, while the variable attitude and subjective norms do not affect it. Further testing indicates that the variable intention to abide affects compliance with taxpayers positively. This study aims to analyze the factors that affect the tax compliance by using Theory of Planned Behavior Approach (TPB). This study used survey design with data collection techniques by using questionnaires, where the selected respondents are taxpayers of individuals and entities registered at the KPP in the city of Palembang. The results showed that the variables that influence the intention to abide positively are the control behavioral variable and moral obligation, while the variable attitude and subjective norms do not affect it. Further testing indicates that the variable intention to abide affects compliance with taxpayers positively.